Penegakan Kedisiplinan dalam Meningkatkan Efektivitas Belajar Santri pada Madrasah Aliyah Dayah Ruhul Islam Anak Bangsa Aceh Besar - Muhammad Rizki (Jurnal Riset dan Pengabdian Masyarakat, 2026)
Discipline is a crucial factor in creating effective learning, particularly in Islamic-based educational institutions such as Islamic boarding school senior high schools (Madrasah Aliyah Dayah). This study aims to analyze the enforcement of discipline in improving students' learning effectiveness at Madrasah Aliyah Dayah Ruhul Islam Anak Bangsa, Aceh Besar and to identify supporting and inhibiting factors in its implementation. This research employs a qualitative approach with a field research design. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that disciplinary enforcement at Madrasah Aliyah Dayah Ruhul Islam Anak Bangsa has been implemented optimally through collaboration between the principal, teachers, and other school stakeholders. Discipline enforcement has positively impacted students' learning effectiveness, although a small number of students still face difficulties in adhering to disciplinary rules due to environmental and family background factors. Therefore, consistent, humane, and collaborative discipline enforcement significantly contributes to improving students' learning effectiveness.